The principles of Islamic education according to Abdul Rahman AlNahlawi in 'Usūl Al-Tarbiyah Al-Islămiyyah wa Asălībuha Fi Al Bayt wa Al Madrasah wa Al Mujtama' / Artini Timbang - Timbang, Artini (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
The principles of Islamic education have privileges that are not possessed by other educational systems. However, in this age, the Muslim community is more influenced by Western theories in everything that is said to be more superior in the West, especially in the field of education. The Muslim community seems to have forgotten that the principles of Islamic education and attention to great personal formation have long been introduced by the Prophet Salallahu 'alaihi wasallam, his companions and the great scholars in Islamic history. This paper aims to shed light on the educational principles of Abdul Rahman Al-Nahlawi, an Islamic scholar who produced several books that are widely cited in the field of education. This study uses a content analysis approach and is only focused on one of the well-known al-Nahlawi's book that has been translated into Indonesian. As a result of this analysis, al-Nahlawi concluded that education in Islam should be based on the Quran and the Sunnah. In addition, there are five basic elements of education that must be taken into consideration by the Muslim community in order to produce a true Muslim generation.